Evaluation of the Correlation Between Bispectral Index Monitorization and Ramsey Sedation Scoring, Michigan Sedation Scoring and Brussels Sedation Scoring - Deveci, Uğur; Bulut, Leyla (My University, 2024)
Objective: Interventional Sedation and Analgesia (ISA) is a common practice for managing pain in pediatric clinics. Monitoring the depth of sedation is crucial for patients undergoing sedation and analgesia. This study aims to determine the correlation between EEG monitoring and the Ramsey Sedation Scale (RSS), Brussels Sedation Scale (BSS), and Michigan University Sedation Scale (MUSS) in monitoring the depth of sedation in patients undergoing ISA for endoscopy and colonoscopy. Material and Method: Thirty-three patients were enrolled in our prospective and analytical study at Fırat University, Faculty of Medicine, Child Health and Diseases Service, between 11.04.2021 and 30.07.2021. Socio-demographic data, vital signs at the start of ISA, and at 5, 10, 15, and 20- minute intervals, along with Glasgow Coma Scale (GCS), BIS, RSS, BSS, and MUSS values were recorded. The compatibility of BIS with RSS, BSS, and MUSS values was evaluated. Results: The median age among the 33 patients was 8±7 years, with a female/male ratio of 1.5. The lowest mean BIS measurements were recorded at the start of the procedure (92±19) and at the 5th minute (79±17). Measurements taken at the 10th, 15th, and 20th minutes were 79±16, 77±19, and 79±17, respectively. No correlation was detected between BIS and RSS, BSS, or MUSS averages at any time point (p=0.446, p=0.938, p=0.219). However, a significant correlation was found between RSS and MUSS (p=0.007). Conclusion: The administration of sedation and analgesia effectively reduces the severity of pain experienced by patients. Additionally, careful monitoring of sedation and analgesia during interventional procedures is critical for preventing complications and ensuring optimal patient outcomes.
Keywords: Child; Bispectral Index; Brussels Sedation Scale; Interventional Sedation Analgesia; Michigan Sedation Scale; Ramsey Sedation Scale